X-ray photoelectron spectroscopy and Raman microscopy of a ferroan platinum crystal from the Kondyor Massif, Russian Far East. Issue 1 (2nd January 2019) - Kloprogge, J. Theo; Wood, Barry J.
Abstract: X-ray Photoelectron Spectroscopy was used to study a ferroan platinum crystal from the Kondyor Massif, Russian Far East. Prior to the X-ray Photoelectron Spectroscopic analyses, the nature of the crystal was confirmed by X-ray diffraction. The survey scan showed mainly the presence of Pt and Fe, with smaller amounts of O and Si. The high resolutions spectra of the Pt 4f and Fe 2p showed 18.3 atom% Fe in the crystal, which puts the composition on the lower boundary for ferroan platinum and confirms earlier analyses using other methods such as Scanning Electron Microscopy-Energy Dispersive X-ray analysis/microprobe. The binding energy of the Pt 4f5/2 was 74.0 eV and Pt 4f7/2 70.5 eV, while the Fe 2p3/2 for metallic Fe was observed at 707.2 eV. The Fe 2p3/2 for metallic Fe was significantly sharper than that of Fe 2p3/2 at 710.7 eV associated with surface material. The Raman spectrum was dominated by the Pt–Pt stretching mode at 253 cm −1 . Changed orientation resulted in the observation of two bands at 127 and 139 cm −1, interpreted as being due to stretching modes of two Pt–Pt bonds with the third bond to Fe and Pt fixed. The presence of Ca-Fe-Al-Mg-Si-O on the surface was probably associated with the presence of a clinopyroxene. These minerals can be expected since the crystal came originally from a clinopyroxenite-dunite matrix. The spectra showed a variety of interferences, e.g. Al 2p with Pt 4f, Mg 2p with Fe 3p, and Ca 2p1/2 with Mg Auger, making exact determinations of the ratios of these elements difficult.